Effects of culture vessels and environments on maturation and germination os somatic embryos of sago palm (metroxylon sagu rottb.) - Kam., Boon Pay (Universiti Malaysia Sarawak (UNIMAS), 2007)
Sago palm (Metroxylon sagu Rottb.) is an important economic species and is now grown commercially in Sarawak. Actively multiplying stage 2 somatic embryos of the sago palm supplied by CRAUN (Crop Research and Application Unit) Research Sdn. Bhd. were used to investigate the effects of culture medium and container as well as culture conditions on maturation and gennination ofsago embryos. The stage 2 somatic embryos were cultured on four different media which were 7CP2 with and without supplement of activated charcoal and DS9 with and without activated charcoal; in each of the three different culture vessels included specimen tube, petri-dish, and conical flask; and placed at three different environments which were low temperature, dark condition, and low light. The somatic embryos were sub-cultured bi-monthly. The results showed that activated charcoal was significantly important to culture embryos ofM. sagu in vitro, and there was slightly better development for somatic embryos cultured on DS9 media compared to 7CP2 media. Besides that, better results were obtained from embryos cultured in conical flask and petri-dish as compared to specimen tube. However, maturation and gennination of sago embryos did not seem to be influenced by the environmental condition.